PENGARUH KOMPENSASI TERHADAP KERJA KARYAWAN YANG DIMEDIASI OLEH KEPUASAN KERJA (STUDI KASUS PADA PT. BPR MITRA BALI ARTHA MANDIRI DI KARANGASEM, BALI) - I Made Astrama (STIMI Handayani Denpasar, 2016)
The purpose of this study was to determine the effect of variableKompensis and job satisfaction to employee performance and job satisfaction asvariable pemediasi, PT BPR MitraBali ArtaMandiri.This study examined the effectis causal because the independent variable (compensation), the dependent variable(Performance Employees), and the mediating variable (job satisfaction). Object ofresearch at PT BPR Mitra Bali Arta Mandiri, using 40 samples (the respondents),while the data were analyzed by means of statistical regression analysis PLS (PartialLeast Square). Based on the analysis it is concluded that the variable compensation,positive and significant effect on employee performance, compensation and significantpositive effect on job satisfaction. The indirect effect of compensation to employeeperformance through employee compensation, greater than direct influence.This means that as the role of Employee Satisfaction on Employee PerformanceCompensation Pemediasi.